(untitled) (Politeja, 2024)
DEVELOPMENT COOPERATION IN THE FACE OF CHALLENGES IN FRAGILE CONTEXTS – AUSTRIA’S COMMITMENT The aim of the paper is to analyse the commitment of Austrian development cooperation in fragile and conflict-affected countries in the context of dynamically changing conditions of international development cooperation, in particular the Hamas terror on Israel and the ongoing Russian war of aggression on Ukraine. The political guidelines and strategies of key actors in Austrian Official Development Assistance (ODA) have been assessed. Humanitarian aid is a key element of Austria’s engagement abroad in response to numerous crises, implemented multilaterally on the ground through UN agendas and Austrian nongovernmental organisations. At the same time, there is a tightening of connections between humanitarian aid and development cooperation in contexts of instability as an expression of Austria’s global responsibility.